Influence of time to diagnosis of severe influenza on antibiotic use, length of stay, isolation precautions, and mortality: a retrospective study. Issue 4 (12th May 2017) - Akers, Isabel E.; Weber, Rainer; Sax, Hugo; Böni, Jürg; Trkola, Alexandra; Kuster, Stefan P.
Abstract: Background: Timely diagnosis of influenza infection in patients might help reduce antibiotic use during influenza seasons and, consequently, antibiotic selection pressure. In this retrospective cohort study, we aimed to evaluate whether time to influenza diagnosis in patients with severe influenza is associated with the duration of antibiotic therapy. Methods: We retrospectively included all hospitalized patients >16 years who tested positive for influenza A or B by polymerase chain reaction during influenza seasons 2013/2014 or 2014/2015 at the University Hospital Zurich. The primary aim was to assess the association between timing of laboratory‐confirmed influenza diagnosis and duration of antibiotic therapy. Secondary outcomes were length of hospital stay, duration of isolation precautions, and mortality. Early diagnosis was defined as laboratory confirmation on the day of or the day after hospital admission or symptom onset. Results: A total of 126 patients were included (median age 57 years). Timing of influenza diagnosis was not associated with the duration of antibiotic treatment, the duration of isolation precautions, or mortality. Early influenza was associated with reduced length of hospital stay (median 7 vs 9 days [ P =.014]) in patients with community‐acquired influenza. Conclusions: Although the duration of antibiotic therapy and mortality were found unaffected by early influenza diagnosis, our data indicate that it is linked with a reduction in the length of hospitalization in patients with community‐acquired influenza. This highlights a need to also fully understand the effect of time to diagnosis of bacterial pathogens on antibiotic prescribing patterns in order to exploit the potential of early influenza diagnosis in patient care.